(untitled) (Research, Society and Development, 2021)
Introduction: Breastfeeding has numerous benefits when correlated with child development and growth. Exclusive breastfeeding until six months provides numerous privileges that ranges from the immune system to family bonds between mother and child, benefiting the newborn´s development. Methodology: 150 children aged 5 to 10 were analyzed using a structed questionnaire to assess their current nutritional status and form of nutrition during lactation. Results and Conclusion: Exclusive breastfeeding for at least one month is a protective factor for weight-related problems (such as underweight for age, overweight or obesity) (p<0,001) and formula breastfeeding for at least one month is an aggravating factor for weight-related problems (p<0,001).